A legalidade como fator de inclusão social da cidadã e do cidadão homossexual - Marinho, Paula Márcia de Castro (2014)
This dissertation is a research about the legality as factor of social inclusion and citizenship for homosexual citizens. Its main scope is to investigate in what measure the legality, or saying the law, is a fundamental element in the brazilian democratic state of law for the extension of citizenship to the homosexual category. This study also has the purpose of analyze the possible necessity for specific treatment of the legal system to homosexual individual; evaluate the need for these new legalities in order to exceed the conditions of subalternity and to include excluded groups in Brazil, and assess the probability that a legally statutory, constantly socially experienced, can corroborate to change the subordinate status of homosexual citizens, provide them social recognition and respect. With this intent, has been done an analysis of the bond that unites modern citizenship with the new legalities built on liberal principles of equality, freedom and belonging in a national community, concurrent to the existence of subaltern social groups destined to have fewer rights. It was appreciated the conflict between the emancipatory and conservative poles around the legal compliance of sexual diversity or with the intent to put obstacle of attempts at social and political emancipation of the class, especially in actions filed in seat of the national legislature. The paper points to the need for legal recognition for to extend citizenship, reduce subordination and include excluded groups. Therefore, it accepts to the symbolic force of legality as an able force to trace ways toward a more equitable and diverse citizenry that includessocial and politically the homosexualities.